1997
DOI: 10.1074/jbc.272.27.17196
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 Is Necessary for Tumor Necrosis Factor α-induced Ceramide Generation in L929 Cells

Abstract: The role of cytosolic phospholipase A 2 (cPLA 2 ) in the regulation of ceramide formation was examined in a cell line (L929) responsive to the cytotoxic action of tumor necrosis factor ␣ (TNF␣). In L929 cells, the addition of TNF␣ resulted in the release of arachidonate, which was followed by a prolonged accumulation of ceramide occurring over 5-12 h and reaching 250% over base line. The formation of ceramide was accompanied by the hydrolysis of sphingomyelin and the activation of three distinct sphingomyelina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(95 citation statements)
references
References 26 publications
(34 reference statements)
6
87
1
1
Order By: Relevance
“…In contrast, we find that CD95L did not induce the formation of ceramide in LN-18 or LN-229 either in the absence or presence of CHX ( Figure 4A). As a positive control, we confirm a significant increase of ceramide in L929 fibrosarcoma cells exposed to TNF-a (Jayadev et al, 1997). Consistent with this negative finding in glioma cells, we observed that inhibitors of acid sphingomyelinase such as desipramine (Hurwitz et al, 1994) or of ceramide synthase such as fumonisin B 1 (Bose et al, 1995), that is, of the key enzymes involved in ceramide generation, had no effect on CD95L-induced apoptosis.…”
Section: No Ceramide Release During Cd95l-induced Glioma Cell Apoptosissupporting
confidence: 75%
“…In contrast, we find that CD95L did not induce the formation of ceramide in LN-18 or LN-229 either in the absence or presence of CHX ( Figure 4A). As a positive control, we confirm a significant increase of ceramide in L929 fibrosarcoma cells exposed to TNF-a (Jayadev et al, 1997). Consistent with this negative finding in glioma cells, we observed that inhibitors of acid sphingomyelinase such as desipramine (Hurwitz et al, 1994) or of ceramide synthase such as fumonisin B 1 (Bose et al, 1995), that is, of the key enzymes involved in ceramide generation, had no effect on CD95L-induced apoptosis.…”
Section: No Ceramide Release During Cd95l-induced Glioma Cell Apoptosissupporting
confidence: 75%
“…The sensitivity of HL-60 cells, which rapidly remodel arachidonate, to CoA-IT inhibition was suggested to be due to the rapid accumulation of the pathway intermediate free AA and its activation of a sphingomyelinase leading to ceramide generation (22). A similar cell death mechanism where the cell's inability to control free AA levels leads to increased ceramide concentration has been suggested to occur after cPLA 2 activation in TNF-sensitive cells (46,47) and in cells treated with cyclooxygenase inhibitors (23). In resting cells where arachidonate-PL remodeling proceeds slowly, pathway intermediates like free AA would accumulate to a lesser extent after CoA-IT inhibition, likely allowing the cell to cope with any released free AA via reacylation into phospholipids or triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…The cell-killing effect of TNF-␣ has been shown to signal through ceramide, and AA stimulated this pathway under different conditions (17,28). To evaluate the involvement of ceramide, we measured the cellular ceramide level after exposure of the cells to exogenous AA (300 M) for 1, 4, and 24 h. At 1 h there was a small increase (less than 2-fold) and at the other times there was no change compared with control cells (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ exerts a cytotoxic effect against certain tumor cells, and release of AA by cPLA 2 has been implicated in this process (13,28). In the cells that overexpressed FACL4 or COX-2, the cell survival after TNF-␣ treatment was increased moderately (not shown), and it was significantly improved in the FACL4͞COX-2 stable cells: the surviving fraction increased from 43.5 to 70.5% (n ϭ 3, P Ͻ 0.001) (Fig.…”
Section: Depletion Of Arachidonic Acid Also Prevents Tnf-␣-mediated Kmentioning
confidence: 99%